Historical structure of the human and rodent periodontium - Mihály, András; Mihály, Eszter (Acta Biologica Szegediensis, 2015)
Adult human dental tissue and young rat jaws with developing teeth were investigated. The tissues were fixed by immersion in 4% buffered paraformaldehyde. Decalcified tissues were embedded into paraffin or sectioned on a freezing microtome. Paraffin sections were stained with hematoxylin and eosin. Frozen sections were stained with calcitonin generelated peptide (CGRP) antibodies using avidin-biotin systems and peroxidase labelling. The histology of the acellular cement and the histology of the periodontal ligament were analyzed and the course of the Sharpey-fibers and the epithelial rests of Malassez were described in human samples. The epithelial sheath of Hertwig in developing rat maxillae and mandibles (postnatal days 1-11) were depicted. The layers of the Hertwig-sheath were described. We observed the numerical increase of CGRP-stained nerve fibers during these postnatal days. The CGRP-stained nerve fibers appeared before the development of the dental root indicating the presence of growth factors which guide the sensory axons. We hypothesize that the epithelial sheath of Hertwig plays essential role in the development of cementoblasts, periodontal fibroblasts and alveolar osteoblasts. Furthermore, the growth factors secreted by the Hertwig-sheath may stimulate the axonal growth, too.